ARMED CONFLICT AS A FATAL THREAT TO CHILD HEALTH AND SOCIAL DEVELOPMENT - Nwosu, Innocent Ahamefule (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
Armed conflict is obstacle to good health and peaceful co-existence in many countries. It is an enemy against children. During Nigeria Civil War (1967-1970), millions of children on the defunct Biafra side died from adverse health conditions. In spite of these, the health/social consequences of that war on children have not been adequately addressed. The study therefore assessed disruption of family lives of the children and diseases that affect them during that war. The study utilized in-depth interviews and complemented it with narrative review of literature on the civil war. It was found that there is a strong relationship between armed conflict and adverse health conditions of children before, during and after war. Therefore, war affects children’s health and social development. The study recommends that serious effort should be made to prevent war or where it is impossible, adequate relief support and medical infrastructures should be in place by national and international governments/agencies.